Identification of novel inhibitor against endonuclease subunit of Influenza pH1N1 polymerase: A combined molecular docking, molecular dynamics, MMPBSA, QMMM and ADME studies to combat influenza A viruses. (December 2018) - Mohseni, Seyed Sajad; Nasri, Fariborz; Davari, Kambiz; Mirzaie, Sako; Moradzadegan, Atousa; Abdi, Fatemeh; Farzaneh, Farhad
Graphical abstract: Highlights: The new potent inhibitor against endonuclease subunit of Influenza pH1N1 Polymerase (PA) is suggested by virtual screening, QMMM, and MD studies. The inhibition mechanism and physicochemical properties of three systems including PA and a mutant PA in free or complex states were evaluated. ADMET analysis showed that compound ZINC15340668 could be a potent inhibitor of therapeutic targets of PA and mutant PA. Further analysis on ZINC15340668 can be carried out through various experimental studies. Abstract: The influenza H1N1 virus is the causative agent of the flu pandemic in the world. Due to the shortage of effective means of control, it is remained the serious threats to public and avian health. To battle the surge of viral outbreaks, new treatments are crucially needed. The viral RNA polymerase, which is responsible for transcription and replication of the RNA genome, is comprised of subunits PA, PB1 and PB2. PA has endonuclease activity and is a well known target for inhibitor and drug design. In the current study, we employed molecular docking, molecular dynamics (MD), MMPBSA, QMMM and ADME studies to find and propose an inhibitor among 11, 873 structures against PA. Our molecular docking, MD, MMPBSA and QMMM studies showed that ZINC15340668 has ideal characteristics as a potent PA inhibitor, and can be used in experimental phase and further development. Also, ADME prediction demonstrated that all physico-chemical parameters are within the acceptable range defined for human use. Molecular mechanism based study revealed that upon inhibitor binding; the flexibility of PA backbone is increased. This observation demonstrates the plasticity of PA active site, and it should be noticed in drug design against PA Influenza A viruses. In the final phase of the study, the efficiency of our proposed hit was tested computationally against mutant drug resistant I38T_PA. Our results exhibited that the hit inhibits the I38T_PA in different manner with high potency.